Blood indices, in-hospital outcome and short-term prognosis in patients with COVID-19 pneumonia - Al-Buthabhak , Karrar; Nafakhi, Hussein; Shukur , Mohammed H.; Nafakhi, Ahmed; Alareedh, Mohammed; Shaghee, Foaad (Monaldi Archives for Chest Disease, 2021)
The predictive role of blood indices in coronavirus disease 2019 (COVID-19) related in-hospital adverse outcomes and post-recovery status is not fully defined. The main aim was to assess the association of complete blood indices measured at baseline with COVID-19 related in-hospital clinical outcomes, including length of hospital and intensive care unit (ICU) stay, receiving mechanical ventilation, degree of lung injury and in-hospital death, and post-recovery status. This retrospective study included patients with newly diagnosed COVID-19 infection from August 20, to September 25, 2020. The initial study cohort included 127 patients with newly diagnosed COVID-19. Of whom 26 patients were excluded, leaving 101 patients for final analysis. low lymphocytes % [Odds ratio and confidence intervals = OR (CI)] [0.2(0.0-0.2, p=0.03] increased the odds of ICU stay length while high platelet mean volume (PMV) [0.9 (1.1-5, p<0.00], high platelet distribution width (PDW) [0.3(0.4-1.9), p<0.00], and low lymphocytes % [0.2 (0.0-0.2), p=0.02] increased the odds of length of hospital stay. Decreased lymphocytes % showed significant independent association with increased risk for mechanical ventilation use [0.9 (0.9-1), p=0.04], extensive degree of lung injury [0.2 (0.1-0.7), p<0.00], and in-hospital death [0.5 (0.3-0.8), p=0.01]. High lymphocytes %[0.9 (0.9-1), p<0.00] and high PMV [0.3 (0.3-0.8), p=0.02] were significantly associated with complete recovery while increased neutrophil % [1 (1-1.1), p=0.04] was associated with increased risk for post recovery fatigue. In conclusion, low lymphocytes % and high neutrophil % are useful markers for predicting adverse in-hospital outcome and post-recovery persistent fatigue, respectively. High PMV and lymphocyte % showed significant association with favorable short-term prognosis.